1991
DOI: 10.1073/pnas.88.24.11515
|View full text |Cite
|
Sign up to set email alerts
|

Expression cloning of a cDNA encoding the bovine histamine H1 receptor.

Abstract: Since Dale and Laidlaw (1) first reported the contraction of smooth muscle by histamine, the pharmacological significance of this phenomenon has been extensively investigated. Three subtypes of histamine receptor (H1, H2, and H3) are known. The H1 receptor was identified by Ash and Schild (2) and H1 receptor antagonists have been used in the therapy of many allergic diseases, including urticaria, allergic rhinitis, pollenosis, and bronchial asthma. In peripheral tissues, the histamine H1 receptor mediates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(154 citation statements)
references
References 33 publications
6
146
0
2
Order By: Relevance
“…The tissue distribution of human Hi-histamine-receptor mRNA was not comparable to that of the bovine, rat and guinea-pig homologues (Yamashita et al, 1991 ;Horio et al, 1993). An additional transcript was specifically and abundantly found in the human brain tissue, whereas no brain specific mRNA was present in the bovine, rat and guinea-pig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The tissue distribution of human Hi-histamine-receptor mRNA was not comparable to that of the bovine, rat and guinea-pig homologues (Yamashita et al, 1991 ;Horio et al, 1993). An additional transcript was specifically and abundantly found in the human brain tissue, whereas no brain specific mRNA was present in the bovine, rat and guinea-pig.…”
Section: Discussionmentioning
confidence: 99%
“…Binding conditions are as described in Materials and Methods. Data are presented as the mean t SD (n 2 3) receptors (Yamashita et al, 1991;Fujimoto et al, 1993;Horio et al, 1993).…”
Section: P L C L F W L S N D Y V a S T A S I F S V F I L C I D R Y R mentioning
confidence: 99%
See 2 more Smart Citations
“…The most direct evidence for the involvement of this residue comes from mutation studies with the &2-adrenoceptor (Horstman et al, 1990) and the dopamine D2-receptor , in which substitution of the aspartate with asparagine (M2-receptor) or alanine (D2-receptor) abolished the regulatory action of Na' on ligand binding. With the histamine HI-receptor the regulation of agonist binding by Na' (Chang & Snyder, 1980) presumably involves in the second transmembrane loop of the HI-receptor cloned from bovine adrenal medulla (Yamashita et al, 1991) or Asp-73 in the rat HI-receptor (Fujimoto et al, 1993). How-ever, antagonist binding can also be modulated by Na+, as originally demonstrated for opiate receptors (Pert & Snyder, 1974;Paterson et al, 1986), and we have reported that Na+ ions distinguish between the binding of two antagonist radioligands to the histamine HI-receptor (Treherne et al, 1991).…”
Section: Introductionmentioning
confidence: 99%